The Use of E-learning Information Educational Environment in University under the Realization of Educational Programmes - Medvedeva, Irina; Martynyuk, Oksana; Pankova, Svetlana; Solovyova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The structure of information educational environment for the support of the students’ mastering the competence-oriented higher educational programmes is considered in the article. The experience of its using is submitted.